Current thinking and new paradigm for COPD. (March 2016) - Welte, Tobias; Chapman, Kenneth R.; Magnussen, Helgo; Miravitlles, Marc
Abstract: During the 2015 European Respiratory Society Congress, a symposium was held on 'Current thinking and new paradigm for COPD'. Through a combination of plenary lectures and interactive panel discussions, experts discussed the recent evidence for chronic obstructive pulmonary disease (COPD) treatment and how this evidence can be applied in clinical practice.